A Meta-Analysis of Gender Group Differences for Measures of Job Performance in Field Studies - Roth, Philip L.; Purvis, Kristen L.; Bobko, Philip (Journal of Management, 2012)
There are multiple views in human resource management and organizational behavior concerning gender differences in measures of job performance. Some researchers suggest that males generally are evaluated higher than females across a variety of situations that include job performance measurement. At the same time, the presence of specific status cues in expectation states theory (EST; similar to the concept of individuating information) suggests that measures of job performance will be more similar than different for males and females. Previous analyses are unclear in their results for the measurement of the construct of job performance because they have included, and/or focused on, additional constructs (e.g., hiring suitability, leadership performance aggregated with leadership satisfaction) or have used student samples in lab experiments. The authors of this article conducted a meta-analysis of job performance measures from field studies. They found that females generally scored slightly higher than males (mean d = −.11, 80% credibility interval of −.33 to .12). Other analyses suggested that, although job performance ratings favored females, ratings of promotion potential were higher for males. Thus, ratings of promotability may deserve further attention as a potential source of differential promotion rates. These findings and processes are discussed within the context of EST.